DGS-based quad element planar array for WLAN application with enhanced performance - Asadullah, G. M.; Islam, Md. Shazzadul; Islam, Md Rafiqul; Sahad, Asif Jamil; Sakib, Md Abu Tayab (Institute of Electrical and Electronics Engineers Inc., 2020)
The proposed assembly comprises of 2×2antenna elements with defected ground structure (DGS) toresonate at 5.8 GHz for WLAN application, where eachantenna element excited by inset feeding technique. TheproposedMIMO arrayhas achieved–10 dB bandwidth of85MHzwith 36.5% reduction inantenna areawithsimilarradiating element. Besides, the proposed design alsoachievedhigh radiation efficiency of 95% with a peak directivity of11.94 dBi. The antenna resonates at the designated frequencywith a minimum return loss of–42dB. The results includeparametric study by subtracting more slots from the groundand placed them in horizontal direction. The obtained antennaarraycan be used for WLAN applicationwith lowmanufacturing cost.